2017
DOI: 10.1080/15459624.2017.1339165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating bioaerosol exposure among bus drivers in the public transport sector

Abstract: Occupational hazards and consequent health problems suffered by drivers in the public transport sector require preventive measures. The aim of this study was to assess the exposure of drivers to microbiological air contamination (airborne bacteria and fungi) in buses. The air in public transport vehicles was examined in autumn, winter and spring. To evaluate the exposure of drivers to bioaerosols, air samples were collected and examined for the total number of bacteria and fungi in the air, the number of mesop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…The microbial aerosol concentrations in studied buses measured before and after the air-conditioning system servicing as well as in outdoor (atmospheric) air are presented in Table 1. The scientific literature review revealed that bioaerosol concentrations in municipal buses generally range between 10 2 -to 10 4 CFU/m 3 [7,9,10,12]. The airborne bacterial and fungal concentrations recorded in bus cabins evaluated in this study before the AC system service were within the above range reaching 4.3×10 2 CFU/m 3 and 2.4×10 2 CFU/m 3 , respectively.…”
Section: Quantitative Analysis Of Bacterial and Fungal Biota In Air Smentioning
confidence: 49%
“…The microbial aerosol concentrations in studied buses measured before and after the air-conditioning system servicing as well as in outdoor (atmospheric) air are presented in Table 1. The scientific literature review revealed that bioaerosol concentrations in municipal buses generally range between 10 2 -to 10 4 CFU/m 3 [7,9,10,12]. The airborne bacterial and fungal concentrations recorded in bus cabins evaluated in this study before the AC system service were within the above range reaching 4.3×10 2 CFU/m 3 and 2.4×10 2 CFU/m 3 , respectively.…”
Section: Quantitative Analysis Of Bacterial and Fungal Biota In Air Smentioning
confidence: 49%
“…At the beginning, the bacteria were identified by Gram staining (111885 Gram-color stain set; Merck KgaA, Germany) (Murray et al 2013) to determine their morphology and, finally, by the biochemical analytical profile index (API) tests (bioMérieux, France). Yeast strains were identified by the API (API 20 C Aux) test.…”
Section: Conventional Methodologiesmentioning
confidence: 99%
“…3), as it was expected, due to less ventilation as the AC is not functioning, as opposed to summer: May-September. Nowakowicz-Dębek et al (2017) have analyzed microorganisms inside public buses in winter, autumn and spring, in Lublin, Poland, and showed that the highest concentration of total bacteria was detected in winter, while the lowest in spring. In contrast, for Lee and Jo (2005) in a study in Daegu, Korea, total bacteria concentration inside buses was higher in summer than in winter, however these comparison must be taken with care as the "summer: May-September" and "winter: November-March" periods were not the same, and the methodology for sampling was also different in each study.…”
Section: Total Bacteria Quantificationmentioning
confidence: 99%
“…In Barcelona, public transport is used every day by more than a half of the city commuters, almost 3 million, on journeys lasting from 30 to 60 minutes every working day. External weather conditions or technologies within the vehicle, such as brake and tire wear, road abrasion, fuel, interior coatings and materials, are also responsible for the indoor air quality (Nowakowicz-Dębek et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation